Negotiating (athletic) femininity: the body and identity in elite female basketball players. Issue 2 (15th March 2017) - Bennett, Erica V.; Scarlett, Louisa; Hurd Clarke, Laura; Crocker, Peter R. E.
Abstract: The purpose of this study was to examine the role of body perceptions in elite women basketball players' negotiation of their athletic and feminine identities in and outside of sport. Semi-structured interviews were conducted with six elite female basketball players and data were analysed using interpretative phenomenological analysis. Findings revealed that some participants perceived their athletic and feminine selves to be separate entities. Their athletic identities came to the forefront in athletic contexts through displays of strength and assertiveness, and their feminine identities were emphasised in social contexts through appearance and dress. Other participants perceived their athletic and feminine identities to be compatible and at the forefront in both athletic and social contexts. Despite their perceptions of the (in)congruence of their athletic and feminine identities, all participants expressed some satisfaction with the instrumental capabilities of their bodies, but desired aesthetic body changes that would increase their compliance with a lean and toned female body ideal. The women also engaged in appearance management through the use of clothing, makeup, and dieting to emphasise their femininity. Media images of women's bodies and coach feedback influenced these body-related perceptions and experiences. Findings contribute to existing research exploring female athlete identity and body image.